Residential aged care nurses: portraits of resilience. Issue 6 (28th October 2016) - Cope, Vicki Catherine; Jones, Bronwyn; Hendricks, Joyce
Abstract : Aim : To explore residential aged care nurses working in interim, rehabilitation and residential aged care perceptions of resilience. Design : Qualitative Portraiture methodology. Inclusion criteria were that all participants were English speaking, registered with the Australian Health Practitioners Registration Authority and had more than five years' experience working in an aged care environment. Three participants were interviewed and employed within a metropolitan interim, rehabilitation and aged care setting. Results : Eight themes were identified: valuing social support; leadership, managing 'self'; 'paying it forward'; passion for the profession; focusing on the positive and the taking on of challenge. Conclusions : This paper focuses on the impact of aged care nursing work on nurses and in particular how the nurses remain resilient in their work environment. Resilience can be developed through education and can sustain professional longevity. Workload stress can be alleviated through the provision of resilience training.